Disconfirmation of Taste as a Measure of Trust in Brands: An Experimental Study on Mineral Water - Elena Kokthi; Ledia Thoma; Reka Saary; Aniko Kelemen-Erdos (Foods, 2022)
The underlying factors of the purchase decision process of bottled mineral water have been a less studied area. The typically related attributes of consumer judgement in the case of low involvement can vary widely, ranging from price sensitivity to habits. However, assessing the role of brand reputation and trust from a sensory perception perspective is not a common approach. This paper examines the impact of trust on consumer value judgements for a frequently consumed beverage such as mineral water. Combining trust and sensory attributes with the Expectation–Disconfirmation Theory (EDT) framework provides insights into the weight of taste, trust and reputation in product evaluation. A tasting experiment was carried out using a representative systematic random sampling method. A mixed method was applied; EDT was used to analyze quantitative data and grounded theory methodology was performed in the case of qualitative data. Results indicate complete assimilation for the most preferred brand and negative contrast for less well-known brands. It can be stated that the applied methodology is suitable as a certain kind of trust measurement and also can function particularly well as a reinforcement and complement to other methodologies (e.g., neuromarketing methods). This study suggests that brand names positively influence value judgment. Origin bounded brands compared to imported brands can help companies mitigate trust issues in developing countries as they convey a particular reputation, which helps reinforce trust.